Nanoplasmonic biosensors for precision medicine - Xiao, Yiran; Zhang, Zongming; Yin, Shi; Ma, Xingyi (Frontiers in Chemistry, 2023)
Nanoplasmonic biosensors have a huge boost for precision medicine, which allows doctors to better understand diseases at the molecular level and to improve the earlier diagnosis and develop treatment programs. Unlike traditional biosensors, nanoplasmonic biosensors meet the global health industry's need for low-cost, rapid and portable aspects, while offering multiplexing, high sensitivity and real-time detection. In this review, we describe the common detection schemes used based on localized plasmon resonance (LSPR) and highlight three sensing classes based on LSPR. Then，we present the recent applications of nanoplasmonic in other sensing methods such as isothermal amplification, CRISPR/Cas systems, lab on a chip and enzyme-linked immunosorbent assay. The advantages of nanoplasmonicbased integrated sensing for multiple methods are discussed. Finally, we review the current applications of nanoplasmonic biosensors in precision medicine, such as DNA mutation, vaccine evaluation and drug delivery. The obstacles faced by nanoplasmonic biosensors and the current countermeasures are discussed.